2022
DOI: 10.1038/s41419-022-04815-8
|View full text |Cite
|
Sign up to set email alerts
|

Bloom syndrome helicase contributes to germ line development and longevity in zebrafish

Abstract: RecQ helicases—also known as the “guardians of the genome”—play crucial roles in genome integrity maintenance through their involvement in various DNA metabolic pathways. Aside from being conserved from bacteria to vertebrates, their importance is also reflected in the fact that in humans impaired function of multiple RecQ helicase orthologs are known to cause severe sets of problems, including Bloom, Werner, or Rothmund-Thomson syndromes. Our aim was to create and characterize a zebrafish (Danio rerio) diseas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…This observation implied that rag1 might play a potential role in maintaining genomic integrity to regulate and prevent premature aging. Furthermore, mutations in the genes atm and blm, which were previously discussed in the context of cancer and germ cell development, also result in decreased lifespans, suggesting that these genes may have multiple functions in the lifespan regulation of living organisms [76,84]. All these studies collectively emphasize the pivotal role of DNA repair mechanisms in aging, illustrating how genomic integrity is closely intertwined with organismal longevity.…”
Section: Agingmentioning
confidence: 72%
See 1 more Smart Citation
“…This observation implied that rag1 might play a potential role in maintaining genomic integrity to regulate and prevent premature aging. Furthermore, mutations in the genes atm and blm, which were previously discussed in the context of cancer and germ cell development, also result in decreased lifespans, suggesting that these genes may have multiple functions in the lifespan regulation of living organisms [76,84]. All these studies collectively emphasize the pivotal role of DNA repair mechanisms in aging, illustrating how genomic integrity is closely intertwined with organismal longevity.…”
Section: Agingmentioning
confidence: 72%
“…A depletion of blm in zebrafish leads to a bias towards male phenotypes with reduced fertility. In the testes of blm mutants, spermatocytes are arrested in meiotic phase I, suggesting that infertility in blm mutants is caused by meiotic arrest of spermatocytes [84]. Taken together, these observations highlight the crucial role of the FA/HR pathway in repairing DNA cross-link for proper germ cell development.…”
Section: Germ Cell Developmentmentioning
confidence: 77%
“…Previous studies have demonstrated that disruption of the DNA damage repair mechanisms promote genomic instability, and lead to increased risks for cancer susceptibility and germline defects across species, such as fly, zebrafish, mouse and human [ 44 , 45 , 46 , 47 ]. For example, the FA pathway is a dominant mechanism for inter‐strand cross‐link repair in vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…BLM gene encodes a 3′‐5′ DNA helicase, which is required for precise double‐stranded DNA break repair, processing of DNA replication intermediates and rDNA metabolism. Impaired function of BLM caused shortened lifespan and reduced fertility in zebrafish, mouse and human [ 46 , 51 ]. HELQ is also a crucial DNA helicase for maintaining genomic stability, which acts through a mechanism distinct from the function of FA pathway [ 29 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here we found 28 factors that may represent perhaps the most important proteins that could mediate the age-controlling aspects of GPR19 biology. These proteins included multiple factors shown to exert a strong regulatory role in the aging process, e.g., DNA damage repair factors BLM [ 207 ], XRCC5 [ 208 ], RECQL4 [ 209 ], FAAP100 [ 210 ], FOXM1 [ 211 ], NUCKS1 [ 212 ], FEN1 [ 213 ]; energy metabolism factors UCP2 [ 214 ], PARP1 [ 215 ], HMOX1 [ 216 ], ARG2 [ 217 ], IDE [ 218 ]; cell cycle/fate control factors CDKN1A [ 219 ], CDK5 [ 220 ], WWC1 [ 221 ], CENPW [ 222 ]; transport and proteostasis regulation factors ZMPSTE24 [ 223 ], HSPA9, also known as Mortalin [ 224 ], SQSTM1 [ 225 ], PPM1L [ 226 ], PICALM [ 227 ]. To assess the degree of specificity of this cohort of GPR19-Aging-associated factors, we tested multiple (n = 10) random datasets the same numerical size as the unbiased aging dataset to assess the potential for random intersections between the GPR19-associated dataset with one the same size as the aging-specific dataset.…”
Section: Functional Gpr19 Molecular Signaturesmentioning
confidence: 99%